2019
DOI: 10.1007/s00125-019-4960-8
|View full text |Cite
|
Sign up to set email alerts
|

In search of causal pathways in diabetes: a study using proteomics and genotyping data from a cross-sectional study

Abstract: Aims/hypothesisThe pathogenesis of type 2 diabetes is not fully understood. We investigated whether circulating levels of preselected proteins were associated with the outcome ‘diabetes’ and whether these associations were causal.MethodsIn 2467 individuals of the population-based, cross-sectional EpiHealth study (45–75 years, 50% women), 249 plasma proteins were analysed by the proximity extension assay technique. DNA was genotyped using the Illumina HumanCoreExome-12 v1.0 BeadChip. Diabetes was defined as tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 37 publications
4
31
0
1
Order By: Relevance
“…HNMT, SIT1, RTN4R, CDCP1, SIGLEC10, IFNLR1 and VSIG4) expand the knowledge about the biochemical manifestations of type 2 diabetes and provides a resource for new candidate biomarkers in this disease area. This study also confirms several previously published associations between key proteins and prevalent diabetes and/or diabetes progression, including PON3, HGF, CTSD, IL1RA, SIGLEC7, LPL, IL6, FGF21, ERBB2, ALDH1A1, GAL4, ADM and FABP4 [ 5 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HNMT, SIT1, RTN4R, CDCP1, SIGLEC10, IFNLR1 and VSIG4) expand the knowledge about the biochemical manifestations of type 2 diabetes and provides a resource for new candidate biomarkers in this disease area. This study also confirms several previously published associations between key proteins and prevalent diabetes and/or diabetes progression, including PON3, HGF, CTSD, IL1RA, SIGLEC7, LPL, IL6, FGF21, ERBB2, ALDH1A1, GAL4, ADM and FABP4 [ 5 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ].…”
Section: Discussionsupporting
confidence: 91%
“…Many of these interactions are mediated through various circulating proteins, including hormones, growth factors, adipokines, cytokines and enzymes [4] . The recent advancements in high throughput technologies for measuring a large number of proteins in a single assay have enabled data-driven discoveries that may offer new insights into the dysregulated metabolic milieu of diabetes [ 5 , 6 ]. There is also a potential for comprehensive protein profiling in personalized medicine, by detecting early signs of disease development and providing simultaneous information on multiple cardiometabolic health indicators in individual patients [7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one of these studies showed a modest improvement in discrimination by adding 3 proteins (MASP, ApoE, and CRP) to the standard clinical model (AUC increased from 0.75 to 0.77). Up to 142 plasma proteins have been associated with prevalent T2D [ 59 •, 60 , 61 ] in cross-sectional studies, which aim to identify differences between T2D patients and well-matched control samples or associations with glycaemic parameters, providing a cost-effective and simple prioritisation strategy. However, these studies suffer from reverse confounding, i.e.…”
Section: Existing Strategies For T2d Prediction Screening and Diagnmentioning
confidence: 99%
“…Systematic causal assessment for protein candidates on T2D had little success at first [ 56 , 60 , 87 ], and only recently, several proteins are suggested to be causally related to T2D (Table 2 ). WFIKKN2 is the only protein identified by more than one study with consistent effect directions.…”
Section: Existing Strategies For T2d Prediction Screening and Diagnmentioning
confidence: 99%